A novel polyurethane prepolymer as toughening agent: Preparation, characterization, and its influence on mechanical and flame retardant properties of phenolic foam. Issue 5 (28th August 2012) - Yang, Hongyu; Wang, Xin; Yu, Bin; Yuan, Haixia; Song, Lei; Hu, Yuan; Yuen, Richard K.K.; Yeoh, Guan Heng
Abstract A novel phosphorus‐ and silicon‐containing polyurethane prepolymer (PSPUP) was synthesized by the chemical reaction of phenyl dichlorophosphate with hydroxy‐terminated polydimethylsiloxane (HTPDMS) and subsequently with toluene‐2, 4‐diisocyanate. The structure of PSPUP was confirmed by Fourier transform infrared spectroscopy and 1H nuclear magnetic resonance. Afterward, a series of phenolic foams (PF) with different loadings of PSPUP toughening agent were prepared. The apparent density and scanning electron microscopy results showed that the addition of PSPUP can increase the apparent density of phenolic foam. The compressive, impact and friability test results showed that the incorporation of PSPUP into PF dramatically improved the compressive strength, impact strength, and reduced the pulverization ratio, indicating the excellent toughening effect of PSPUP. The limiting oxygen index of PSPUP modified phenolic foams remained a high value and the UL‐94 results showed all samples can pass V0 rating, indicating the modified foams still had good flame retardance. The thermal properties of the foams were investigated by thermogravimetric analysis under air atmosphere. Moreover, the thermal degradation behaviors of the PF and PSPUP/PF were investigated by real‐time Fourier transform infrared spectra. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013